Independent measurement of the total active 8B solar neutrino flux using an array of 3He proportional counters at the Sudbury Neutrino Observatory. - Aharmim, B; Ahmed, SN; Amsbaugh, J; Anthony, A; Banar, J; Barros, N; Beier, E; Bellerive, A; Beltran, B; Bergevin, M; Biller, S; Boudjemline, K; et al. (American Physical Society, 2008)
The Sudbury Neutrino Observatory (SNO) used an array of 3He proportional counters to measure the rate of neutral-current interactions in heavy water and precisely determined the total active (nu_x) 8B solar neutrino flux. This technique is independent of previous methods employed by SNO. The total flux is found to be 5.54_-0.31;+0.33(stat)-0.34+0.36(syst)x10(6) cm(-2) s(-1), in agreement with previous measurements and standard solar models. A global analysis of solar and reactor neutrino results yields Deltam2=7.59_-0.21;+0.19x10(-5) eV2 and theta=34.4_-1.2;+1.3 degrees. The uncertainty on the mixing angle has been reduced from SNO's previous results.